PERUBAHAN FUNGSIONAL ANYAMAN PANDAN DARI PRODUK TIKAR MENJADI PRODUK TAS - SRI NINGSIH, Dra. Jupriani, M.Sn, Dra. Ernis, M.Pd (Serupa The Journal of Art Education, 2014)
This thesis has the goal of (1) to develop products especially in the area of woven pandanus Indragiri Hulu, so again by consumer demand and emerging new works can be seen that the development of craft woven itself, (1) In order for society more responsive, especially artisans can utilize natural resources, so it can sustain the economy.The method of making this work after the emergence of the next idea to make a sketch of an alternative product bag, after the execution of the selected sketch then make bag patterns to be created. creator began to assemble the bag and then in sewing. The technique used is by using the technique of sewing machines, sewing techniques and paste techniques. In this thesis the author tries to create new product forms are not yet available in the market.Keywords: Craft, Woven Pandan, Products Bags.